Multimedia communications directions and innovations - Gibson, Jerry D. (San Diego : Academic Press, 2001)
The rapid advances and industry demands for networked delivery of information and pictures through computer networks and cable television has created a need for new techniques and standards for the packaging and delivery of digital information. Multimedia Communications presents the latest information from industry and academic experts on all standards, methods and protocols. Internet protocols for wireless communications, transcoding of Internet multimedia for universal access, ATM and ISDN chapters, videoconferencing standards, speech and audio coding standards, multi-casting and image compression techniques are included. * Latest Internet protocols for wireless communications * Transcoding of Internet multimedia for universal access * ATM and ISDN chapters * Videoconferencing standards * Speech and audio coding standards * Multi-casting * Latest image compression techniques.
ch. 1. Multimedia communications: source representations, networks, and applications / Jerry D. Gibson -- ch. 2. Future telecommunication networks: traffic and technologies / Leonid G. Kazovsky, Giok-Djan Khoe, and M. Oskar van Deventer -- ch. 3. Speech coding standards / Andreas S. Spanias -- ch. 4. Audio coding standards / Chi-Min Liu and Wen-Whei Chang -- ch. 5. Still image compression standards / Michael W. Hoffman and Khalid Sayood -- ch. 6. Multimedia conferencing standards / David Lindbergh -- ch. 7. MPEG-1 and -2 compression / Tom Lookabaugh -- ch. 8. MPEG-4 and MPEG-7 / Jerry D. Gibson -- ch. 9. ATM network technology / Yoichi Maeda and Koichi Asatani -- ch. 10. ISDN / Koichi Asatani and Toshinori Tsuboi -- ch. 11. Video-on-demand broadcasting protocols / Steven W. Carter, Darrell D.E. Long, and Jehan-Franπcois Pγaris -- ch. 12. Internet telephony technology and standards overview / Bernard S. Ku -- ch. 13. Wideband wireless packet data access / Justin Chuang, Leonard J. Cimini, Jr., and Nelson Sollenberger -- ch. 14. Internet protocols over wireless networks / George C. Polyzos and George Xylomenos -- ch. 15. Transcoding of the Internet's multimedia content for universal access / Richard Han and John R. Smith -- ch. 16. Multicasting: issues and networking support / Upkar Varshney.
Includes bibliographical references and index.
Keywords: Telecommunication; Multimedia systems; Digital communications; Interactive multimedia; Electronic books